Theoretical developments and applications of non-integer order systems : 7th Conference on Non-Integer Order Calculus and Its Applications, Szczecin, Poland /: 7th Conference on Non-Integer Order Calculus and Its Applications, Szczecin, Poland. ([2016]) - Unknown
No abstract available